PERSEPSI PESERTA DIDIK TERHADAP KEPRAKTISAN KOMIK BAHAN AJAR BERBASIS CANVA FOR EDUCATION - Ningrum, Andi Alfina Listya (Bahterasia : Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2025)
Digital-based teaching materials are a manifestation of the Industrial Revolution 4.0 in the field of Education, where the use of digital-based teaching materials is one of the main competencies that must be carried out by teachers in delivering material to students. Comics are one of the teaching materials that can present material visually and aesthetically so that it is interesting to read by students and can optimize learning. This study aims to describe the perceptions of students at SMA Negeri 1 Bantaeng regarding the practicality of Teaching Material Comics based on Canva for Education. The type of research used is qualitative descriptive research through data collection instruments in the form of questionnaires. From the data collected, all respondents totaling 34 students stated that comics that utilize Canva for Education have good quality to be used as teaching materials in terms of content, attractiveness of appearance, and language aspects.